Tanggung Jawab Notaris atas Pemalsuan yang Dilakukan oleh Klien dalam Proses Pembuatan Akta - Ayu Rizkie; Muhammad Arifin; Ramlan Ramlan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Notary is a public official who is authorized to make an authentic deed whose authority has been determined by law, in fact there are not a few notaries who commit violations or crimes in making a deed so as to result in the emergence of criminal acts, it can be seen in the decision of the Padang District Court Number 535 / Pid.B / 2013 / PN.Pdg, in this case the notary public commits an act of forgery so that the notary is liable to criminal liability against him. This writing aims to review and analyze the legal consequences of the deed which in the process of making that contain elements of forgery and analyze criminal liability against a notary in the Padang District Court's decision No. 535 / Pid.B / 2013 / PN.Pdg. the results of this paper show that the legal consequences of the deed which in the process of making it contain elements of forgery can be canceled, the cancellation of a deed is a sanction against legal actions that contain elements of juridical defects (causes of cancellation) and also has no legal consequences since the cancellation of parties referred to in the deed. The criminal liability against the notary public in the decision of the Padang District Court Number 535 / Pid.B / 2013 / PN.Pdg, has fulfilled both elements in terms of the ability to be responsible and errors, and the absence of forgiving reasons, all three elements have been fulfilled so that the legal notary as the defendant can be held liable for criminal action against him.